2003
DOI: 10.1007/s00426-003-0157-2
|View full text |Cite
|
Sign up to set email alerts
|

Positive facial expressions are recognized faster than negative facial expressions, but why?

Abstract: Three experiments examined the recognition speed advantage for happy faces. The results replicated earlier findings by showing that positive (happy) facial expressions were recognized faster than negative (disgusted or sad) facial expressions (Experiments 1 and 2). In addition, the results showed that this effect was evident even when low-level physical differences between positive and negative faces were controlled by using schematic faces (Experiment 2), and that the effect was not attributable to an artifac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

62
219
7
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(290 citation statements)
references
References 40 publications
62
219
7
2
Order By: Relevance
“…For instance, participants take longer to count the number of facial features in displays of negative than of positive schematic faces (Eastwood, Smilek, & Merikle, 2003), to respond to the gender of negative than of positive faces (Purcell, Stewart, & Skov, 1998), or to respond to the color of a negative than of a positive face (White, 1996). The findings are also broadly consistent with a number of studies that have found people to be faster and more accurate at identifying happy faces than negative (fearful, angry, sad, or disgusted) faces (Juth et al, 2005;Kirita & Endo, 1995;Leppänen & Hietanen, 2004;Palermo & Coltheart, 2004). For instance, concluded that happy faces were identified more rapidly and required less effort to encode than negative faces.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, participants take longer to count the number of facial features in displays of negative than of positive schematic faces (Eastwood, Smilek, & Merikle, 2003), to respond to the gender of negative than of positive faces (Purcell, Stewart, & Skov, 1998), or to respond to the color of a negative than of a positive face (White, 1996). The findings are also broadly consistent with a number of studies that have found people to be faster and more accurate at identifying happy faces than negative (fearful, angry, sad, or disgusted) faces (Juth et al, 2005;Kirita & Endo, 1995;Leppänen & Hietanen, 2004;Palermo & Coltheart, 2004). For instance, concluded that happy faces were identified more rapidly and required less effort to encode than negative faces.…”
Section: Discussionsupporting
confidence: 88%
“…To do so, we had to avoid the most negative images from the IAPS since they tend to be more highly arousing than the positive images. We also attempted to avoid pictures displaying close-ups of people's faces since there is evidence for a processing advantage for happy faces (Amir, Elias, Klumpp, & Przeworski, 2003;Juth, Lundqvist, Karlsson, & Öhman, 2005;Kirita & Endo, 1995;Leppänen & Hietanen, 2004). Within these constraints, we wanted to maximize the valence difference between our stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…However, faster responses to pleasant stimuli are in line with the assumption that pleasant stimuli facilitate the approach system [28]. Faster reaction times when making recognition decisions on pleasant pictures have already been reported in Bradley et al [2] and a number of recent studies have shown faster responses to pleasant stimuli in choice reaction tasks, particularly when affirmative button presses were required [31,35,51]. If indeed the response bias in favour of pleasant pictures at present is mediated by familiarity, there is clearly the possibility that 'real-life familiarity' determined this response bias.…”
Section: Discussionsupporting
confidence: 70%
“…Happy and angry face expressions are more efficiently recognized in humans and require less time for processing (Hess et al, 1997;Leppänen and Hietanen, 2004;Fox et al, 2000). OT appears to further improve this fast recognition process in humans below the threshold of conscious awareness (Schulze et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our central hypothesis was that OT would enhance the recognition of emotions overall. We further expected that emotion expressions that are easier to read, such as happy and angry faces, would show effects of OT enhancement at earlier rather than later exposure intervals, where ceiling effects may be more common (Hess et al, 1997;Leppänen and Hietanen, 2004;Fox et al, 2000).…”
Section: Introductionmentioning
confidence: 99%